Collected marine litter — A growing waste challenge. (March 2018) - Schneider, Falk; Parsons, Sophie; Clift, Sally; Stolte, Andrea; McManus, Marcelle C.
Abstract: Marine litter, in particular plastic debris, poses a serious threat to marine life, human health and the economy. In order to reduce its impact, marine litter collections such as beach clean-ups are frequently conducted. This paper presents a systematic review of temporal developments, geographical distribution, quantities and waste treatment pathways of collected marine litter. Results from over 130 studies and projects highlight the worldwide increase in collection efforts. Many of these are in wealthy countries that do not primarily contribute to the problem. Over 250 thousand tonnes, have already been removed, but there is little or no information available regarding how this waste is treated or used post collection. This paper highlights the need for a whole-system quantitative assessment for the collection and waste treatment of marine litter, and identifies the challenges associated with utilising this waste in the future. Highlights: 132 studies (103 from scientific literature) on marine litter were reviewed. Analysis showed that marine litter collections are increasingly reported worldwide. It is calculated that over 250 thousand tonnes of marine litter have been removed. None of the 103 scientific studies include any marine litter waste management. A full system quantitative assessment of collected marine litter impacts is needed.